Studies on Iran and the Caucasus. In honour of Garnik Asatrian - Bläsing, Uwe.; Arekelova, Victoria.; Weinreich, Matthias. (Middle East and Islamic Studies E-Books Online, Collection 2015, ISBN: 9789004287464., 2015)
This unique collection of essays by leading international scholars gives a profound introduction into the great diversity and richness of facets forming the study of one of earth's most exciting areas, the Iranian and Caucasian lands. Each of the 37 contributions sheds light on a very special topic, the range of which comprises historical, cultural, ethnographical, religious, political and last but not least literary and linguistic issues, beginning from the late antiquity up to current times. Especially during the last decennia these two regions gained greater interest worldwide due to several developments in politics and culture. This fact grants the book, intended as a festschrift for Prof. Garnik Asatrian, a special relevance. Contributors: Victoria Arakelova; Marco Bais; Uwe Bläsing; Vahe S. Boyajian; Claudia A. Ciancaglini; Johnny Cheung; Viacheslav A. Chirikba; Matteo Compareti; Caspar ten Dam; Desmond Durkin-Meisterernst; Kaveh Farrokh; Aldo Ferrari; Ela Filippone; Khachik Gevorgian; Jost Gippert; Nagihan Haliloğlu; Elif Kanca; Pascal Kluge; Anna Krasnowolska; Vladimir Livshits; Hirotake Maeda; Irina Morozova; Irène Natchkebia; Peter Nicolaus; Antonio Panaino; Mikhail Pelevin; Adriano V. Rossi; James R. Russell; Dan Shapira; Wolfgang Schulze; Martin Schwarz; Roman Smbatian; Donald Stilo; Çakır Ceyhan Suvari; Giusto Traina; Garry Trompf; Matthias Weinreich; Eberhardt Werner and Boghos Zekiyan